Ammonia Emission Model for Whole Farm Evaluation of Dairy Production Systems. Issue 4 (1st July 2014) - Rotz, C. Alan; Montes, Felipe; Hafner, Sasha D.; Heber, Albert J.; Grant, Richard H.
Abstract : Ammonia (NH3 ) emissions vary considerably among farms as influenced by climate and management. Because emission measurement is difficult and expensive, process‐based models provide an alternative for estimating whole farm emissions. A model that simulates the processes of NH3 formation, speciation, aqueous‐gas partitioning, and mass transfer was developed and incorporated in a whole farm simulation model (the Integrated Farm System Model). Farm sources included manure on the floor of the housing facility, manure in storage (if used), field‐applied manure, and deposits on pasture (if grazing is used). In a comprehensive evaluation of the model, simulated daily, seasonal, and annual emissions compared well with data measured over 2 yr for five free stall barns and two manure storages on dairy farms in the eastern United States. In a further comparison with published data, simulated and measured barn emissions were similar over differing barn designs, protein feeding levels, and seasons of the year. Simulated emissions from manure storage were also highly correlated with published emission data across locations, seasons, and different storage covers. For field applied manure, the range in simulated annual emissions normally bounded reported mean values for different manure dry matter contents and application methods. Emissions from pastures measured in northern Europe across seasons and fertilization levels were also represented well by the model. After this evaluation, simulations of a representative dairy farm in Pennsylvania illustrated the effects of animal housing and manure management on whole farm emissions and their interactions with greenhouse gas emissions, nitrate leaching, production costs, and farm profitability.